Cu2O thin films grown by magnetron sputtering as solar cell absorber layers. (September 2022) - Lakshmanan, A.; Alex, Zachariah C.; Meher, S.R.
Abstract: In the present work, Cu2 O thin films were deposited by reactive magnetron sputtering at different substrate temperatures ranging from 300 to 673 K. The structural, optical and electrical properties of Cu2 O films have been studied for their potential use as solar cell absorber layers. X-ray diffraction and Raman studies confirmed the cubic phase of Cu2 O. X-ray photoelectron spectroscopy shows the presence of minority CuO phase at the surface. The surface morphology at different substrate temperatures has been studied using the scanning electron microscopy and atomic force microscopy. The optical property of Cu2 O thin films has been evaluated with the help of transmittance spectroscopy, photoluminescence spectroscopy and spectroscopic ellipsometry. The optical band gap obtained from the transmittance spectroscopy is found to be in the range of 1.82–2.07 eV. All the films exhibit p -type conductivity with a typical carrier concentration of ∼10 14  cm −3 . Highlights: Single phase Cu2 O thin films by reactive magnetron sputtering. Change in the preferential growth along (111) plane to (200) plane at higher substrate temperatures. Cu2 O thin films deposited at 373 K have the highest crystallinity. Absorption coefficient of 10 5  cm −1 suggests potential application as solar cell absorber layer. Cu2 O/ZnO heterojunctions based solar cell exhibits rectifying characteristics.